Effect of CCNB1 silencing on cell cycle, senescence, and apoptosis through the p53 signaling pathway in pancreatic cancer - Zhang, Hui; Zhang, Xuan; Li, Xun; Meng, Wen‐Bo; Bai, Zhong‐Tian; Rui, Shao‐Zhen; Wang, Zheng‐Feng; Zhou, Wen‐Ce; Jin, Xiao‐Da (Journal of cellular physiology, 2019)
Pancreatic cancer (PC) is a serious malignancy with high mortality and poor prognosis due to nonspecific incipient symptoms and early metastasis. Also, increasing evidence indicates that a panel of genes is newly identified in the pathogenesis of PC. As is a regulatory subunit, elevated cyclin B1 (CCNB1) expression has been detected in different cancers including PC. This study is designed to investigate the effects of CCNB1 silencing on cell cycle, senescence, and apoptosis through the p53 signaling pathway in PC. PC tissues and normal pancreatic tissues were collected. Cells were transfected and assigned into different groups. The expressions of CCNB1, p53, MDM2, Bax, caspase‐9, caspase‐3, and p21 in tissues and cells were detected by reverse transcription quantitative polymerase chain reaction and western blot analysis. β‐Galactosidase staining, MTT assay, and flow cytometry were conducted to test cell senescence, proliferation, cell cycle, and apoptosis. PC tissues showed higher expressions of CCNB1 and MDM2 and lower expressions of Bax, caspase‐9, caspase‐3, and p21. Cells transfected with shCCNB1 had lower expressions of CCNB1 and MDM2, whereas higher expressions of Bax, caspase‐9, caspase‐3, p53, and p21. The shCCNB1 group had decreased proliferation and S‐phase cell proportion and increased apoptosis, senescence, and G0/G1‐phase cell proportion. The PFT‐α group showed higher expressions of MDM2 and lower expressions of Bax, caspase‐9, caspase‐3, p53, and p21. The PFT‐α group had increased proliferation and S‐phase cell proportion and declined apoptosis, senescence, and G0/G1‐phase cell proportion. CCNB1 silencing inhibits cell proliferation and promotes cell senescence via activation of the p53 signaling pathway in PC. CCNB1 silencing inhibits cell proliferation and promotes cell senescence via activation of the p53 signaling pathway in pancreatic cancer.